Rodumna (Roanne, Loire), le village gallo-romain Évolution des mobiliers domestiques - Genin, Martine; Lavendhomme, Marie-Odile (Documents d'archéologie française, 1997)
This study gives an account of the results of the archaeological excavations of the Gallo-Roman village at Roanne (Rodumna). The research is based mainly on 22 assemblages of material dating from the 1st century B.C. to the 3rd century A.D., including glassware, iron and bronze objects, and above all an exceptional corpus of pottery. Detailed analysis of the pottery and its relationship with the rest of the material enabled a chronology to be established. Using criteria such as frequency, use, variety of pottery production, datation, origins, etc., this chronology was found to be in continuity with previously studied Gaulish horizons. A series of illustrations places the material within the context of its discovery. The results of this study lead to an outline of the economic development of Rodumna - a small, rural town, built of clay and wood, very much in keeping with Gaulish tradition. This new volume in the dAf collection continues the study of the Gaulish occupations of Roanne begun in the recently published dAf 62. These two volumes, along with the publication on Feurs (dAf 14), constitute an exceptional documentation about the antique Segusiavi region.